Media Digital Profetik: Reposisi Media Pembelajaran PAI Berbasis Literasi Digital Qur’ani - Umar; Kuryani (Ri'ayah: Jurnal Sosial dan Keagamaan, 2025)
The development of digital technology has caused a paradigm shift in the landscape of Islamic Education (PAI). On one hand, digital-based learning media offers various benefits in the breadth of interaction and information access. On the other hand, it creates certain challenges in the maintenance of spiritual values in character. This article reviews the literature on the trend of research on digital learning media for PAI during the 2021-2025 period. The results show that most studies on innovations in e-learning platforms, social media, and interactive applications in PAI learning, especially during the pandemic, have proved to increase student access and motivation to learn. On the other hand, only a few studies integrated the value of Islamic prophetic teaching into the use of such media. This article introduces the concept of Prophetic Digital Media as a conceptual framework that integrates technology (techne), ethics (ethos), and spirituality (spiritus) grounded in Qur'anic digital literacy. This way, digital media in PAI are not merely technical tools but also a da'wah tool and a means of internalizing values. The study concludes with a conceptual model of “Prophetic Digital Media”, which is expected to become a new paradigm in developing PAI learning media combining the strengths of digital innovation with ethical and spiritual foundations according to Islamic teachings.